2015
DOI: 10.3354/meps11512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pCO2 on spatial competition between the corals Montipora aequituberculata and Porites lutea

Abstract: We tested the hypothesis that ocean acidification (OA) affects spatial competition among scleractinian corals. Competitive ability was evaluated indirectly by linear extension of Porites lutea and Montipora aequituberculata placed in intraspecific, interspecific, and control pairings (paired with dead coral skeleton) and exposed to ambient (~400 µatm) and elevated (~1000 µatm) pCO 2 in experiments conducted in Moorea, French Polynesia, and Okinawa, Japan. High pCO 2 had no effect on linear extension of M. aequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Conversely, Tanner (1997) showed that growth of Acropora hyacinthus and P. damicornis was suppressed under interspecific competition (again, consistent with our study), but did not quantify effects of intraspecific competition44. The only other studies, as far as we are aware, that have compared the effects of intra- and interspecific competition found comparable growth suppression under both types of competition instead of the much greater effect of interspecific competition observed here313245. We suggest these contrasting results are due to differences in study duration; our competition trials ran for 1 year compared with 3–4 weeks in Evensen et al 31.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Conversely, Tanner (1997) showed that growth of Acropora hyacinthus and P. damicornis was suppressed under interspecific competition (again, consistent with our study), but did not quantify effects of intraspecific competition44. The only other studies, as far as we are aware, that have compared the effects of intra- and interspecific competition found comparable growth suppression under both types of competition instead of the much greater effect of interspecific competition observed here313245. We suggest these contrasting results are due to differences in study duration; our competition trials ran for 1 year compared with 3–4 weeks in Evensen et al 31.…”
Section: Discussionsupporting
confidence: 84%
“…The only other studies, as far as we are aware, that have compared the effects of intra- and interspecific competition found comparable growth suppression under both types of competition instead of the much greater effect of interspecific competition observed here313245. We suggest these contrasting results are due to differences in study duration; our competition trials ran for 1 year compared with 3–4 weeks in Evensen et al 31. and Evensen & Edmunds (2016)32.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…) that it is unclear to what extent long‐standing rules determining the outcome of spatial competition (e.g., Lang ; Buss & Jackson ) can inform projections of future community structure (Evensen et al. ). Spatial competition involving Caribbean octocorals is particularly interesting in this regard, because the ecology of some reefs appears to favor increased octocoral abundances (Ruzicka et al.…”
Section: Discussionmentioning
confidence: 99%
“…Here we extend our analyses of the effects of OA and coral-coral interactions on coral growth (Evensen et al, 2015;Evensen and Edmunds, 2016) by testing the hypothesis that colony density affects the physiology of Pocillopora verrucosa (Ellis and Solander 1786) under OA conditions. Treatment effects were evaluated from the summed physiological performance of multiple colonies placed in discrete spatial arrangements within a flume (after Vogel and LaBarbera, 1978) held at a constant flow speed.…”
Section: Introductionmentioning
confidence: 95%